PRODUKTIVITAS PERTANAMAN CAMPURAN RUMPUT UNGGUL DENGAN LEGUM LOKAL PADA LAHAN GALIAN C DI KABUPATEN KARANGASEM - Budiasa, I K.M.; I W. Wirawan; I W. Suarna (Udayana University, 2019)
This research to be carried out in the dryland area at Karangasem Regency with the aim of increasing forage productivity quantitavely and in quality and also can be available sustainably. Feed plants are one of the potentials that can be developed on critical land as an effort to increase land productivity so that over land conversion or over exploitation of land that has a negative impact on the enviroment can be minimized. As well as the sand quarry area, which the community mines as wide as posible for reasons of less productive even though the mining doesn’t get permission by the local goverment because it it a protected area and wear absorption. The experiment will use 2 types superior grass, namely Paspalum atratum and Panicum maximum cv Trichogume, and one type of local legume that has been adaptive to the local enviroment, namely Centrocema pubescens. The purpose of research is to get information about Productivity of Paspalum atratum and Panicum maximum Cv Trichoglume Mixed Cropping with Centrocema pubescense, both from the argonomic and nutritional aspect. The experimental design that will be used is block design that consists of 3 groups as replication and 6 treatment, so that there will bw 18 plots (18 research unit). The results of study showed that the growth of grass in the Passpalum atratum monoculturally was better then Panicum maximum grass, as well as the nutrient content. Better growth also occurs in mixed Paspalum maximum grass planting with Centrocema pubescens compare to Panicum atratum with Centrocema pubescens. In the planting of the mixture of both types of grass with legume Centrocema pubescens it was concluded that, the types of grass of Paspalum atratum is more dominant than the Panicum maximum. Keyword: Paspalum atratum, Panicum maximum, Centrocema pubescens, sand quarry, mixed cropping